2017
DOI: 10.1557/mrs.2017.210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pressure on the structure of glass and its material properties

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Such manipulation of the ordering changes the glass properties, but unlike crystalline solids where symmetry rules, characterizing the nature of this order remains an open challenge. Consequently, there is a structure-versusproperties puzzle in need of a solution for understanding basic issues such as the structural precursors for crystallization in glass 2 and the mechanisms of densification [3][4][5] for guiding the development of new technological materials [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such manipulation of the ordering changes the glass properties, but unlike crystalline solids where symmetry rules, characterizing the nature of this order remains an open challenge. Consequently, there is a structure-versusproperties puzzle in need of a solution for understanding basic issues such as the structural precursors for crystallization in glass 2 and the mechanisms of densification [3][4][5] for guiding the development of new technological materials [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The glasses formed under pressure were recovered to ambient conditions to give permanently densified materials [6][7][8][9]13 , thus facilitating the experimental exploration of different glass structures along with the associated dynamics and thermodynamics. The glass structure was probed by combining high-energy X-ray diffraction with neutron diffraction, and the dynamical and thermal properties of the material were measured by using inelastic neutron scattering (INS) and calorimetry, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing defect density further, the article by Salmon and Huang 40 discusses the inherently disordered nature of glasses that makes investigations into its structural response a complex task. Much ground has, however, been covered in recent years in the characterization of glasses at all length scales.…”
Section: Glasses Under Pressurementioning
confidence: 99%
“…The structural changes in glasses induced by pressure can substantially modify their mechanical, optical, electrical and thermal properties. [1][2][3][4][5][6][7] The structures of silicate, 8 borate, 9,10 borosilicate 11 and germanate 12,13 glasses have been investigated in situ by high pressure X-ray and neutron diffraction and Raman spectroscopy and it is reported that Si-O, B-O and Ge-O coordination in the glass network increases signicantly on compression. Glasses usually recover completely from high pressure conditions, and this helps to make fracture-resistant materials.…”
Section: Introductionmentioning
confidence: 99%